2022
DOI: 10.1111/cas.15527
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for venous thromboembolism, bleeding, and death in colorectal cancer (Cancer‐VTE Registry)

Abstract: The impact of venous thromboembolism in Japanese colorectal cancer patients has not been elucidated. This prespecified subanalysis of the Cancer‐VTE Registry aimed to report venous thromboembolism and event data after 1 year of follow‐up in 2477 patients with colorectal cancer and investigate risk factors of venous thromboembolism. Of 2477 patients, 158 (6.4%) had venous thromboembolism in venous thromboembolism screening at enrollment. Asymptomatic distal deep‐vein thrombosis accounted for 123/158 (77.8%) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
0
7
2
Order By: Relevance
“…These tissue factors can convert PLT into thrombin, which in turn aggravate the severity of bleeding caused by the clotting system, leading to a prolonged time required for plasma coagulation. This relationship between PLT levels and VTE differs from the findings of Masataka Ikeda et al., 11 who reported a correlation between higher PLT levels and the presence of VTE in univariable analysis. The variation in the study sample could account for this inconsistency.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These tissue factors can convert PLT into thrombin, which in turn aggravate the severity of bleeding caused by the clotting system, leading to a prolonged time required for plasma coagulation. This relationship between PLT levels and VTE differs from the findings of Masataka Ikeda et al., 11 who reported a correlation between higher PLT levels and the presence of VTE in univariable analysis. The variation in the study sample could account for this inconsistency.…”
Section: Discussioncontrasting
confidence: 99%
“…While the proportion of patients in Stage IV was less than patients in Stages II and III in the Masataka Ikedal et al. 's study 11 . Furthermore, our results revealed that patients with VTE were associated with lower APTT level.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Venous thromboembolism (VTE), which manifests itself as deep vein thrombosis (DVT) and/or pulmonary embolism (PE), is a frequent and severe complication in individuals with colorectal cancer (CRC), particularly in those who undergo surgery. 1 Both tumor and surgical factors independently contribute significantly to the risk of VTE. 2 It is important to note that VTE is the leading cause of postoperative mortality in patients with CRC.…”
Section: Backg Rou N Dmentioning
confidence: 99%